2016
DOI: 10.1515/hukin-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maximum Isometric Strength and Ball Velocity in the Tennis Serve

Abstract: The aims of this study were to analyze the relationship between maximum isometric strength levels in different upper and lower limb joints and serve velocity in competitive tennis players as well as to develop a prediction model based on this information. Twelve male competitive tennis players (mean ± SD; age: 17.2 ± 1.0 years; body height: 180.1 ± 6.2 cm; body mass: 71.9 ± 5.6 kg) were tested using maximum isometric strength levels (i.e., wrist, elbow and shoulder flexion and extension; leg and back extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 38 publications
3
49
0
1
Order By: Relevance
“…Because of the aforementioned characteristics, it is commonly been accepted that these strokes are affected by several parameters such as technique (Roetert et al, 2009a,b), anthropometrics (Sögüt, 2014;Bonato et al, 2015), strength, power (Baiget et al, 2016;Fett et al, 2018;Palmer et al, 2018) biological (Sanchís-Moysi et al, 2010), and range of movement (ROM) characteristics (Palmer et al, 2018), making the action of a multifactorial nature. Several studies have focused on biomechanical and kinematic factors influencing hitting performance (Elliott et al, 1995;Roetert et al, 2009a,b), establishing the speed of the racquet head, internal rotation of the upper arm, wrist flexion and moment of ball impact as some of the major contributors to generate velocity (Elliott et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the aforementioned characteristics, it is commonly been accepted that these strokes are affected by several parameters such as technique (Roetert et al, 2009a,b), anthropometrics (Sögüt, 2014;Bonato et al, 2015), strength, power (Baiget et al, 2016;Fett et al, 2018;Palmer et al, 2018) biological (Sanchís-Moysi et al, 2010), and range of movement (ROM) characteristics (Palmer et al, 2018), making the action of a multifactorial nature. Several studies have focused on biomechanical and kinematic factors influencing hitting performance (Elliott et al, 1995;Roetert et al, 2009a,b), establishing the speed of the racquet head, internal rotation of the upper arm, wrist flexion and moment of ball impact as some of the major contributors to generate velocity (Elliott et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding strength values, literature traditionally has focused on analyzing isokinetic data at certain joint positions and degrees that mimic the serve action (Ellenbecker and Roetert, 2003), obtaining moderate positive correlations especially on those positions that resemble the serve motion. More recently, investigations have also aimed to assess strength values adding maximal isometric strength testing to experimental methods, especially in the shoulder complex (Cools et al, 2014;Baiget et al, 2016;Fett et al, 2018;Hayes et al, 2018). When assessing SV, it has been accepted as a contributor to velocity production, but few investigations have aimed to the relationship between maximal isometric strength and forehands or backhands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 IR and ER strength of the shoulder muscles has also been related to performance in tennis, more specifically with serve speed, considered the most important shot in competitive tennis. 24 In this regard, Baiget et al 25 observed a relationship between shoulder IR isometric strength levels and serve speed. Moreover, previous authors have found a relationship between ball velocity and elbow and shoulder injuries in baseball players.…”
mentioning
confidence: 98%
“…Kovacs [1] argues that there may not be a significant difference between elite and sub-elite tennis players in terms of aerobic capacity because of the specific nature of tennis game which requires more anaerobic energy use. Aerobic capacity differences may not be often seen between divisions of those sports athletes where anaerobic energy use is more intense, but it should be taken into consideration that VO 2max values of such racket sports athletes may have significant differences related to the intensity of the training or competition [21]. These results could be explained by the fact that players competing with the sport of anaerobic content would not be able to make any specific training to improve their aerobic variable.…”
Section: Discussionmentioning
confidence: 99%